A Multiomics Approach Unravels New Toxins With Possible In Silico Antimicrobial, Antiviral, and Antitumoral Activities in the Venom of Acanthoscurria rondoniae - Câmara, Guilherme A.; Nishiyama-Jr, Milton Y.; Kitano, Eduardo S.; Oliveira, Ursula C.; Silva, Pedro I. da; Junqueira-de-Azevedo, Inácio L.; Tashima, Alexandre K. (Frontiers in Pharmacology, 2020)
The Araneae order is considered one of the most successful group among venomous animals in the world. An important factor for this success is the production of venoms, a refined biological fluid rich in proteins, short peptides and cysteine-rich peptides (CRPs). These toxins may present pharmacologically relevant biological actions, as antimicrobial, antiviral and anticancer activities, for instance. Therefore, there is an increasing interest in the exploration of venom toxins for therapeutic reasons, such as drug development. However, the process of peptide sequencing and mainly the evaluation of potential biological activities of these peptides is laborious, considering the low yield of venom extraction and the high variability of toxins present in spider venoms. Here we show a robust methodology for identification, sequencing, and initial screening of potential bioactive peptides found in the venom of Acanthoscurria rondoniae. This methodology consists in a multi-omics approach involving proteomics, peptidomics and transcriptomics analyses allied to in silico predictions of antibacterial, antifungal, antiviral and anticancer activities. Through the application of this strategy, a total of 92,889 venom gland transcripts were assembled and 84 novel toxins were identified at the protein level, including 7 short peptides and 10 fully sequenced CRPs (belonging to 7 toxin families). In silico analysis revealed that 7 CRPs families have potential antimicrobial or antiviral activities, while 2 CRPs and 4 short peptides are potentially anticancer. Taken together, our results demonstrate an effective multi-omics strategy for the discovery of new toxins and in silico screening of potential bioactivities. This strategy may be useful in toxin discovery, as well as in the screening of activities for the vast diversity of molecules produced by venomous animals.